Hydrolysis of palm oil mill effluent using enzymes from spent mushroom substrate of Pleurotus pulmonarius (FR.) QUEL / Nurul Anisa Mat Yunan - Nurul Anisa , Mat Yunan (2020)
Mushroom cultivation and palm oil industry in Malaysia have contributed to the large volumes of lignocellulosic residues. Lignocellulolytic enzymes profiles (lignin peroxidase, laccase, xylanase, endoglucanase, and β-glucosidase) of Pleurotus pulmonarius (parents strains UMP001 and UMP 002, and the hybrid UMH004) during growth in sawdust substrate bags were investigated. The enzymes extracted from the spent mushroom substrate (SMS) of the strain with the highest enzymes productivity was used to hydrolyse palm oil mill effluent (POME). Optimization of parameters for POME hydrolysis to release reducing sugar was conducted using central composite design (CCD) of response surface methodology (RSM). The potential of hydrolysed POME to produce biohydrogen using acclimatized POME sludge as the inoculum was determined. The productivities of the concentrated enzymes obtained from the eleventh-week old SMS of UMH004 for lignin peroxidase, laccase, xylanase, endoglucanase and β-glucosidase were 214.1 U g-1, 4.1 U g-1, 2.3 U g-1, 14.6 U g-1, and 915.4 U g-1, respectively. Enzymatic hydrolysis of POME using concentrated enzymes yielded four times higher reducing sugar (4.7 g L-1) than hydrolysis using the crude enzymes, (1.1 g L-1). Meanwhile, under the optimized condition using RSM (12 hours, 10% enzyme loading (v/v) at pH 5.4), 3.82 g L-1 of reducing sugar yield was achieved, which was consistent with the predicted reducing sugar yield, (3.76 g L-1). Incubation time and enzyme loading factors had significant effects (p < 0.05) on the POME hydrolysis. The F-value of 38.41 from analysis of variance (ANOVA) indicated that the model could predict the optimum experimental parameters. Batch fermentation of hydrolysed POME yielded 23 times higher volume of biohydrogen when compared to non-hydrolysed raw POME.